Bogusław Miedziński jako współtwórca i propagator założeń konstytucji kwietniowej (1930-1936) - Adamczyk, Arkadiusz (Acta Universitatis Lodziensis. Folia Historica, 2001)
Bogusław Miedziński - one of the most famous political activists and publicists of the interwar period - greatly contributed to the final shape of the April constitution. His role as a creator of that constitution is so far overlooked by the historians. Miedziński used to be elected a general budget referent during the third cadence of the Polish parliament and became the main author of those articles of the constitution that concerned the budget’s matters. Probably it was also him who created the articles connected with the superior authority over the military forces. A lot of his valuable remarks influenced the final text of the constitution. Both in parliament and out of it Bogusław Miedziński, played the roll of the defender of the constitution in the debates with the opposition. He successfully faced his antagonists who were often even better educated and much more politically experienced than he. As an editor-in-chief of semi-official governmental newspaper “Gazeta Polska” he contributed much in popularisation of the ideas of April constitution among public opinion. This article aims at showing the political tools used by Bogusław Miedziński - as a member of an elite that governed Poland in 1930s - in his attempts to introduce the reforms of the political system of the state.